An indicator-based approach to assess sustainability of port-cities and marine management in the Global South - Dinah A. E. Ogara; Joji Morishita; Peter J. Davies; Maina Mbui; Majambo Gamoyo; Nashon Njoroge; Isaac Otieno Chann; Benson Senelwa Igesa; Stephen Odhiambo Ochieng (Frontiers in Marine Science, 2023)
Ports and neighbouring cities function as connectors between land and water and have long accommodated a substantial flow of goods and services. Port cities in the Western Indian Ocean (WIO) region and the Global South (GS) are rapidly and inevitably expanding as the demand for global trade increases. However, this expansion has numerous impacts on the surrounding marine ecosystem and the socio-economic livelihoods of local communities. We propose a framework to evaluate the sustainability of port cities in the WIO region and more broadly for cities in the GS. Through an exploratory approach, a systematic literature review (SLR) was undertaken to identify existing themes on port city and marine ecosystem sustainability indicator frameworks. The results revealed a strong bias towards sustainability publications designed for port cities in Global North. The approach developed from this study focuses on the socio-economic and environmental attributes relevant to ports in the WIO region and for GS countries. This draws from the Drivers, Pressures, States, Impacts and Responses (DPSIR) framework and includes 78 indicators. The indicators are designed to identify and report on the complex land and sea interdependencies of port cities. To test the validity of these indicators their interdependencies were examined through a Causal Network (CN) structure which identified 12 priority DPSIR CN. These were also mapped to the UNSDGs enabling the wider applicability and transferability of the framework. The resulting framework enables port cities in emerging economies to establish robust sustainable reporting systems and provides a framework that offers a unique lens for evaluating interactions embedded in the land and sea continuum.